Children and youth in armed conflict - Nilsson, Ann-Charlotte (Raoul Wallenberg Institute human rights library, 2013)
This is a book that students and professionals from different disciplines and backgrounds, including from academia, international organisations, non-governmental organisations, the medical community, governments, etc., will find to be a valuable resource in their quest to learn more about an area of study that has long been neglected.